2017
DOI: 10.1007/s10646-017-1814-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance genes in surface water of eutrophic urban lakes are related to heavy metals, antibiotics, lake morphology and anthropic impact

Abstract: Urban lakes are impacted by heavy human activities and represent potential reservoirs for antibiotic resistance genes. In this study, six urban lakes in Wuhan, central China were selected to analyze the distribution of sulfonamide resistance (sul) genes, tetracycline resistance (tet) genes and quinolone resistance (qnr) genes and their relationship with heavy metals, antibiotics, lake morphology and anthropic impact. sul1 and sul2 were detected in all six lakes and dominated the types of antibiotic resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(54 citation statements)
references
References 41 publications
2
42
1
1
Order By: Relevance
“…The results indicated that the emergence of resistance genes were deduced by multiple factors, rather than solely caused by the abuse of antibiotics in this system. Many studies indicated that ARGs were correlated with many factors Jiao et al, 2017;Yang et al, 2017). According to previous investigation, correlation between tet genes and tetracyclines were considerably weak in municipal wastewater treatment plant (Gao et al, 2012b).…”
Section: Resultsmentioning
confidence: 98%
“…The results indicated that the emergence of resistance genes were deduced by multiple factors, rather than solely caused by the abuse of antibiotics in this system. Many studies indicated that ARGs were correlated with many factors Jiao et al, 2017;Yang et al, 2017). According to previous investigation, correlation between tet genes and tetracyclines were considerably weak in municipal wastewater treatment plant (Gao et al, 2012b).…”
Section: Resultsmentioning
confidence: 98%
“…Today, antibiotics are not only used as medicine for humans but are also widely used in animal husbandry and aquaculture. However, antibiotics that are unintentionally discharged into the environment pose a great threat to ecosystems and human health [27] [28]. These antibiotics can accumulate in food webs and, even more alarming, antibiotic resistance genes (ARGs) can be transferred between environmental bacteria and human pathogens [28] [29] [30] [31].…”
Section: Introductionmentioning
confidence: 99%
“…The abundant and universal ARGs in rivers and lakes are related to sulfonamide, tetracycline, Beta-Lactamase, macrolides, quinolone, streptomycin, efflux pumps gene and Class I integrons, vancomycin, ampicillin, florfenicol resistance genes are also appeared (Jiang et al 2013;Basso et al 2014;Stange et al 2016;Suhartono and Savin 2016;Yang et al 2017Yang et al , 2018Zhang et al 2017;Su et al 2018). The ARGs will neutralize the benefit antibiotics once given to human beings (Baker 2015;Hiltunen et al 2017).…”
Section: Discussionmentioning
confidence: 99%